Long-term endurance training increases serum cathepsin S and decreases IL-6 and hsCRP levels. Issue 21 (2nd November 2017) - Sponder, Michael; Campean, Ioana-Alexandra; Emich, Michael; Fritzer-Szekeres, Monika; Litschauer, Brigitte; Bergler-Klein, Jutta; Graf, Senta; Strametz-Juranek, Jeanette
ABSTRACT: Cathepsin S (CS) was shown to play a key role in cancer progression, atherosclerosis, heart valve disease, insulin resistance and diabetes mellitus. The present prospective study aimed to investigate the influence of sports on CS, interleukin-6 (Il-6) and high-sensitivity C-reactive protein (hsCRP) levels. Ninety-eight of 109 participants completed the study. Ergometries were performed at baseline and after 8 months to evaluate/quantify the performance gain. Blood samples were taken at baseline and every 2 months. CS was measured by ELISA (enzyme-linked immunosorbent assay). Compared to the control group (mean performance gain −3.41 ± 4.62%) we observed a significant physical-activity-induced increase of CS levels (3.45–3.73 ng · ml −1 ; P  = 0.027) and a significant decrease of Il-6 (2.43–1.91 pg · ml −1 ; P  = 0.031) and hsCRP-levels (0.11–0.09 mg · dl −1 ; P  = 0.001) in the intervention group (mean performance gain: 12.13 ± 6.32%). Furthermore, the tendency of the progression was significant for CS and Il-6 ( P  = 0.002/0.033). We could show a significant sports-induced decrease of the classic inflammation parameters hsCRP/Il-6, probably expressing a downregulation of permanently prevalent inflammation processes. Simultaneously CS levels increased significantly. Our results show that increasing CS amounts are not simply to equal with an enhanced inflammation status and might even have beneficial effects on inflammation and angiogenesis.